Role of Hydrogen Abstraction Reaction in Photocatalytic Decomposition of High Energy Density Materials; Journal of Physical Chemistry C; Vol. 120, iss. 43 - Tsyshevsky R. V. Roman Vitaljevich; Zverev A. S. Anton Sergeevich; Mitrofanov A. Yu. Anatoliy Yuryevich; Iljyakova N. N. Nataljya Nikolaevna; Kostyanko M. V. Mikhail Vladimirovich; Luzgarev S. V. Sergey Valentinovich; Garifzyanova G. G. Gyuzel Gabdulbarovna; Kuklya M. M. Mayya Mikhaylovna (2016, 2016)
Title screen